Ureteroureteral anastomosis for endometriosis involving the ureter: Case series and literature review. Issue 3 (September 2019) - Goggins, Emily R; Wong, Marron; Lindsey, Alexis; Einarsson, Jon I; Cohen, Sarah L
Introduction: The purpose of this study was to review operative management of endometriosis involving the ureter. Materials and methods: Retrospective case series of three patients undergoing resection of ureteral endometriosis with ureteroureterostomy for endometriosis involving the ureter by minimally invasive gynecologic surgeons between 2007 and 2018 at a large academic medical center in the Northeastern United States. A literature review was conducted to find cases with a similar approach. Results: Three cases of ureteral endometriosis surgically managed at our institution with ureteroureteral anastomosis were identified. Ureteral endometriosis was identified preoperatively by hydroureteronephrosis on imaging. Intrinsic ureteral endometriosis was confirmed by pathology in two cases; extrinsic endometriosis was grossly visualized in one case. Operative times ranged from 300 to 387 min. Estimated blood loss ranged from 150 to 250 mL. There were no intraoperative complications. A total of 151 cases with a similar approach were described in the literature. Recurrence of obstructive uropathy occurred in 11 cases. Conclusion: Ureteral endometriosis is a rare complication with several management options. Ureterectomy with ureteroureterostomy has been described in the literature and in three cases at our institution with low complication rates and rare stricture formation. This technique can be successful in the management of ureteral endometriosis and warrants further investigation.